2005
DOI: 10.1113/jphysiol.2005.091280
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interactions between Ca2+ entries through Ltype Ca2+ channels and Na+–Ca2+ exchanger in normal and failing rat heart

Abstract: We used confocal Ca 2+ imaging and the patch-clamp technique to investigate the interplay between Ca2+ entries through L-type Ca 2+ channels (LCCs) and reverse-mode Na + -Ca 2+ exchange (NCX) in activating Ca 2+ -induced Ca 2+ release (CICR) from the sarcoplasmic reticulum (SR) in cardiac myocytes from normal and failing rat hearts. In normal myocytes exposed to N (6),2 -O-dibutyryl adenosine-3 ,5 -cyclic monophosphate (db-cAMP, membrane-permeable form of cAMP), the bell-shaped voltage dependence of cytosolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…PKA-dependent phosphorylation and Ca 2ϩ -dependent allosteric effects on NCX resulting from crosstalk between L-type Ca 2ϩ channel and NCX has also been noted in ventricular cells. 19,20 This supports the idea that NCX may generate a larger inward current in response to LCRs. …”
supporting
confidence: 72%
“…PKA-dependent phosphorylation and Ca 2ϩ -dependent allosteric effects on NCX resulting from crosstalk between L-type Ca 2ϩ channel and NCX has also been noted in ventricular cells. 19,20 This supports the idea that NCX may generate a larger inward current in response to LCRs. …”
supporting
confidence: 72%
“…1b, pink bars). These results suggested that NHE1 could use proton efflux in exchange for sodium influx; the neighboring NCX1 could then take the local high sodium to drive calcium influx that triggered CICR and calcium oscillation (27)(28)(29)(30)(31). Such combined NHE1-NCX1 activity appeared to also function in human platelets, since either EIPA or bepridil could effectively inhibit calcium oscillation induced by the cells' binding to Fg (Fig.…”
Section: Net Calcium Influxes Generated By Combined Nhe1-ncx1 Effectsmentioning
confidence: 94%
“…31 However, on the basis of this explanation, one would expect the unresolved influx to be greater in isoprenaline than control and this is not the case.…”
Section: Venetucci Et Al Ryanodine Receptor As An Antiarrhythmic Stramentioning
confidence: 96%